Learning Through Screens: A Literature Review on the Role of Visual and Digital Media in Early Childhood Education - Amallia, Raysha; Suriansyah , Ahmad; Amelia , Rizky (International Journal of Research in Education, 2025)
The use of visual and digital media in early childhood education has emerged as a pedagogical response to technological advancements that demand innovation in the learning process. However, prior research often addresses fragmented aspects, such as specific tools or short-term effects, without offering a comprehensive synthesis. To address this gap, the present study systematically reviews the roles, effectiveness, challenges, and implementation strategies of visual and digital media in ECE. A descriptive qualitative method was employed, using a systematic literature review guided by the PRISMA framework. Data were collected from several scientific databases such as Google Scholar, SINTA, and ResearchGate, focusing on publications from the last five years. The analysis reveals that visual and digital media such as animated videos, interactive flashcards, digital storybooks, and smart boards significantly support children's cognitive, linguistic, motor, literacy, numeracy, and socio-emotional development. These media enhance engagement, motivation, and conceptual understanding through multisensory, interactive experiences. However, several challenges persist, including infrastructure limitations, low digital literacy among educators and parents, and psychological risks such as screen addiction and reduced social interaction. Addressing these issues requires strategies such as using age-appropriate content, regulating screen time, fostering teacher–parent collaboration, and ongoing teacher training. The study concludes that visual and digital media are effective pedagogical tools when implemented thoughtfully and contextually. It offers practical insights and evidence-based recommendations to help educators and policymakers integrate digital media in early learning environments responsibly and sustainably.